Temperature Compensation of the MEMS-Based Electrochemical Seismic Sensors - Chao Xu (Micromachines, 2021)
Electrochemical seismic sensors that employ liquid as their inertial masses have the advantages of high performances in the low-frequency domain and a large working inclination. However, the surrounding temperature changes have serious impacts on the sensitivities of the sensors, which makes them unable to work as expected. This paper studied the temperature characteristics of electrochemical seismic sensors based on MEMS (micro–electro–mechanical systems), and analyzed the influences of the temperature effects on the open-loop and closed-loop amplitude-frequency curves. Most importantly, the temperature compensation circuits based on thermistors were developed, which effectively adjusted pole frequencies and sensitivity coefficients, and finally realized the real-time temperature compensation for both open-loop and closed-loop measurements for the first time. The results showed that in the temperature range of −10 °C ~ +40 °C, and with the 3 dB bandwidth range of 0.01 Hz ~ 40 Hz, the change of the maximum sensitivity was reduced from about 25 dB before temperature compensation to less than 2 dB after temperature compensation.